Pembuatan Aplikasi Wakaf Berbasis Mobile Untuk Masjid Fathur Rahman Menggunakan Metode Extreme Programming - Ramadhan Wal Iqram; Edy Rahman Syahputra; Edrian Hadinata (CV MEDAN TEKNO SOLUSI, 2023)
Waqf is one of the acts of worship in Islam. Through waqf, Muslims can set aside a portion of their wealth for the benefit of the community, especially for the construction and maintenance of mosques. Masjid Fathur Rahman is one of the mosques located in the Binjai area, North Sumatra. This study developed a mobile-based waqf application for Masjid Fathur Rahman using the Extreme Programming method. The aim is to facilitate waqf donations and improve the efficiency of fundraising. The application development is made with two types of applications: a web application for mosque administrators and a mobile application for waqif. The success achieved by this application is inseparable from the advantages of the Extreme Programming method, which ensures a fast and structured application development process, increasing transparency and accountability in waqf management. As a result, the application created can be completed quickly and the application runs well so that the waqif can carry out waqf through the mobile waqf application.